Pedagogical software tools as a methodological basis for improving the acting competence of teachers (Journal of Pedagogical Inventions and Practices, 2026)
This article examines pedagogical software tools as a methodological basis for developing teachers' ICT competencies. It provides a scientific analysis of the processes of digital transformation in education and the possibilities of innovative pedagogical technologies.